KINERJA RUMAH SAKIT DENGAN PENDEKATAN BALANCED SCORECARD PADA RUMAH SAKIT UMUM NEGARA KABUPATEN JEMBRANA - Ni Putu Srinadi Yastini; I Putu Santika; I Wayan Terimajaya; Ni Luh Sili Antari (Fakultas Ekonomi Universitas Warmadewa, 2025)
This study aims to analyze hospital performance using the Balanced Scorecard approach at the Jembrana District General Hospital. The objectives of this study are to analyze performance from the financial perspective, customer perspective, internal business perspective, and learning and growth perspective. The population in this study consists of all patients and employees of the General Hospital. The sample size used was 184 employees and 90 patients. The analysis results found that 1) The performance of the State General Hospital, as assessed from the financial perspective, showed poor performance. The average financial performance of the State General Hospital from 2022 to 2024 was -10.89 percent. 2) The performance of the State General Hospital, assessed from the customer perspective, showed good performance, where patients of the State General Hospital expressed satisfaction with the services provided, as indicated by an average score of 91.83 percent, 7.66 percent were very satisfied, and the remaining 0.51 percent were moderately satisfied. 3) The performance of the State General Hospital, assessed from the internal business process perspective, showed good performance. Where BOR (Bed Occupancy Ratio) is in the poor category, AvLOS (Average Length of Stay) is in the very good category, BTO (Bed Turn Over) is in the very good category, TOI (Turn Over Interval) is in the good category, NDR (Net Death Rate) is in the poor category, and GDR (Gross Death Rate) is in the poor category. And 4) The performance of the State General Hospital was evaluated from the perspective of learning and growth, showing good performance in the indicators of commitment, education and training, and recognition. The recommendations in this study suggest that the management of the State General Hospital should improve the hospital's financial performance and enhance the internal business perspective, particularly in improving the performance of BOR (Bed Occupancy Ratio), NDR (Net Death Rate), and GDR (Gross Death Rate)